Enhancing the sensitivity of a chaos sensor for Internet of Things - Kadhim, Hayder Natiq; Kamel Ariffin, Muhammad Rezal; Md. Said, Mohamad Rushdan; Banerjee, Santo (Elsevier BV, 2019)
Implementing chaotic systems in various applications such as sensors and cryptography shows that the sensitivity and complexity of these systems are highly required. Beside that, many existing chaotic systems exhibit low sensitivity, limited chaotic or hyperchaotic behavior, and low complexity, and this can give a negative effect on the chaos-based sensors applications. To address this problems, we present a cosine chaotification technique to enhance the chaotic characteristics of discrete systems. The proposed technique applies the cosine function as nonlinear transform to the output of a discrete system. As a typical example, we apply it on the classical 2D Hénon map. Performance evaluations show that the proposed technique can change the chaotic and non-chaotic states of the 2D Hénon map to the hyperchaotic state with extremely high complexity performance. Additionally, sensitivity dependence results, such as cross-correlation coefficient, number of non-divergent trajectories, and the change of complexity demonstrate that the enhanced Hénon map has higher sensitivity than the classical map. That means, the proposed technique would be very useful to enhance the employed systems in chaos-based sensors applications.